Remarks on Retirement - Bartley, S. Howard (Canadian Journal of Counselling and Psychotherapy, 2012)
This is a discussion of retirement as viewed from a scholar's standpoint. It pictures a true scholar as a self-ordained individual who does not look forward to a point at which he voluntarily abandons his life's work. He recognizes that part of his life is that of earning aliving, but optimally in academia one's life work and earning a living can be two aspects o fa single endeavor. He does recognize that human powers wane, but he rebels at segmenting his life into unlike periods as implied in the typical retirement concept, but holds to a single goal regardless of the viscissitudes of the workaday world. He believes that this ideal can actually be put into practice both from the standpoint of institutions and individuals. The first thing is getting this ideal understood from the institutional standpoint. There it is a task of how to identify and treat scholars.